1992
DOI: 10.1212/wnl.42.8.1631
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory function in essential tremor

Abstract: Olfactory function, assessed by the University of Pennsylvania Smell Identification Test, was normal in essential tremor (ET) patients and significantly reduced in patients with Parkinson's disease (PD). This finding further supports a lack of association between ET and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 0 publications
3
51
0
4
Order By: Relevance
“…The clinical impairment, evaluated by ETCES, did not correlate to UPSIT scores. Those results are agreeable to researches that evaluated olfactory identification in ET 15,18,20 and it was not found, in this ET group, the mild abnormalities reported by louis and co-workers 19,21 . These authors tested 37 ET patients with a 40 identification odor set and reported mild changes on olfactory discrimination, being that ET patients showed a medium score of 29 and controls of 31.9.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The clinical impairment, evaluated by ETCES, did not correlate to UPSIT scores. Those results are agreeable to researches that evaluated olfactory identification in ET 15,18,20 and it was not found, in this ET group, the mild abnormalities reported by louis and co-workers 19,21 . These authors tested 37 ET patients with a 40 identification odor set and reported mild changes on olfactory discrimination, being that ET patients showed a medium score of 29 and controls of 31.9.…”
Section: Discussionsupporting
confidence: 89%
“…A Brazilian research showed a compromising on olfactory identification on Pd through UPSIT in 80% of patients (medium score 5.7 in Pd vs 9.1 in controls 17 ). researches that used UPSIT described mild abnormalities or normal results on ET and early changes on Pd 15,[18][19][20][21] . The objective of this research was to evaluate the olfactory identification in 40 ET patients, comparing them to 89 controls and correlate UPSIT scores to clinical and epidemiological data.…”
mentioning
confidence: 99%
“…Therefore, this nonmotor finding may be used as a premotor test to identify an at-risk group for PD, but it is certainly not diagnostic. The finding of hyposmia differentiates PD from some other parkinsonian disorders such as progressive supranuclear palsy [14] and vascular parkinsonism [15], and normal olfaction is found in most studies of essential tremor [16][17][18][19].…”
Section: Olfactionmentioning
confidence: 99%
“…Since the early 1990s, it was demonstrated that olfactory deficits could distinguish sporadic PD from essential tremor, dystonic tremor and progressive supranuclear palsy (PSP) 25 . Later, this same conclusion was determined with respect to multiple system atrophy (MSA), cortico basal degeneration and monogenic parkinsonism related to mutations in the PINK1 and PARK2 genes 26,27 while cases with mutations in the LRRK2 gene have intermediate results 28,29 .…”
Section: Olfactory Deficitmentioning
confidence: 99%